Impact of comorbidities and body mass index on the outcomes of allogeneic hematopoietic cell transplantation in myelofibrosis: a study on behalf of the Chronic Malignancies Working Party of EBMT - Polverelli, Nicola; Bonneville, Edouard F.; de Wreede, Liesbeth C.; Koster, Linda; Kröger, Nicolaus Martin; Schroeder, Thomas; Peffault de Latour, Régis; Passweg, Jakob; Sockel, Katja; Broers, Annoek E. C.; Clark, Andrew; Dreger, Peter; et al. (American journal of hematology, 2024)
Investigating the evaluation of eligibility for transplant in myelofibrosis (MF): The role of HCT-CI and BMI. HCT-CI emerges as a key prognostic factor, while BMI shows limited impact. This study expands insights for better clinical decision-making in MF allo-HCT.
Zuerst veröffentlicht: 22. Februar 2024
Gesehen am 05.08.2024